The effect of blowing ratio on film cooling effectiveness using cylindrical and row trenched cooling holes with alignment angle of 90 degrees - Che Sidik, Nor Azwadi (Hindawi Publishing, 2014)
This paper presents the effects of blowing ratio on film cooling performance adjacent to the combustor endwall using cylindrical and row trenched cooling holes with alignment angle of 90 degrees. A three-dimensional representation of a Pratt and Whitney gas turbine engine was simulated and analysed using a commercial finite volume package FLUENT 6.2.26. The combustor simulator was designed to combine the interaction of two rows of dilution jets, which were staggered in the streamwise direction and aligned in the spanwise direction. As a result, the combustor with row trenched holes gave almost doubled cooling performance compared to the baseline case. In addition, the film cooling layer was increased at high blowing ratio, and thus it enhanced the cooling performance.